A union of Iraqi States from failure to sustainable security - Baker, Pauline H. (Emirates lecture series, 2008)
This publication is based on a lecture presented on November 5, 2007"--T.p. verso. This paper looks at Iraq from the failed states perspective with a view toward avoiding this worst-case scenario. It examines trends over the last five years and concludes by proposing a vision for the countrys future based on a framework that would allow the varying sects to live together in peace without genocidal revenge, sectarian domination, foreign occupation or a regional proxy war